Google search trends for itch in Europe: a retrospective longitudinal study. (17th January 2021) - Pereira, M.P.; Ziehfreund, S.; Rueth, M.; Ewering, T.; Legat, F.J.; Lambert, J.; Elberling, J.; Misery, L.; Brenaut, E.; Papadavid, E.; Garcovich, S.; Evers, A.W.M.; et al.
Abstract: Background: Itch is a common symptom in the general population. Affected individuals often do not seek medical consultation and rely on Internet searches to obtain information regarding their itch. Objectives: The aim of this study was to attain insights into common concerns of the general population regarding itch can by analysing itch‐related Internet search behaviour. Methods: Google AdWords Keyword Planner was used to assess search volumes for itch‐related terms in 15 European countries between September 2014 and August 2018. All identified keywords were qualitatively categorized. Itch‐related terms were descriptively analysed and are shown as number of searches/100 000 inhabitants. Results: The search volume for the keyword 'itch' per 100 000 inhabitants was highest in Northern Europe, followed by Eastern, Central and Southern Europe. In 4/15 countries, itch was searched for more often in the autumn/winter months compared to in the spring/summer months. Most itch‐related terms were related to dermatological conditions such as inflammatory skin diseases (e.g. psoriasis, atopic dermatitis), allergic or immunologic conditions (e.g. urticaria), and infectious diseases or infestations (e.g. scabies). In terms of body location, genitoanal itch dominated the searches. Symptoms and signs related to itch, possible non‐dermatological aetiologies, and treatment options were also among the most searched terms. Conclusions: These analyses provided for the first time insights into the search behaviour patterns related to itch across Europe. People from Northern and Eastern Europe are more likely to seek online information regarding itch. Causes for the itch, especially dermatological conditions, and genitoanal itch are the most important concerns for Internet users. This unconventional and inexpensive method identifies medical needs of people beyond the medical setting, including people who do not seek medical consultation. Accordingly, the data could be used to guide public health interventions and manage respective inhabitants' medical needs.